Design and fabrication of a cocoyam (Colocasia esculenta) peeling machine - Audu, Balami Ayuba; Musa, Dauda Solomon; Mohammed, I. S.; Agunsoye, J. K.; Abu, H.; Abubakar, I.; Ahmad, Desa (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The processing of cocoyam tubers for industrial or human use involves different operations of which peeling is the major problem. This study was aimed at designing, fabricating and carrying out performance evaluation of a cocoyam peeling machine, taking into consideration some physical and mechanical properties of the cocoyam tubers. The machine was evaluated based on the following parameters which includes; throughput capacity and peeling efficiency at the speeds of 400 rpm, 700 rpm and 933 rpm. Results revealed that, for all the speeds tested in the experiment, the corresponding peeling efficiencies of the machine were 50%, 64% and 68% respectively while that of the throughput capacities were 63.20 kg/hr, 84.90 kg/hr and 112.92 kg/hr respectively. It was observed that 933 rpm speed was the most suitable speed for the operation of this machine, as it had higher peeling efficiency of 68% with a throughput capacity of 112.92 kg/hr. These results showed appreciable improvement over manual method which is 20 – 35 kg/hr.